(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes the process of formation, types, and main areas of activity of cultural and educational institutions in Uzbekistan during the Soviet period. It reveals the features of their functions, substantive differences, and their role in cultural policy within rural and urban environments. The mechanisms of ideological influence on public consciousness through cultural institutions are also examined. Using the example of “red teahouses,” the article analyzes the adaptation of traditional social spaces to the Soviet cultural system.